Lockdowns and Telework: Psychological and Work-Related Consequences - Chênevert, Denis; Fournier, Pierre-Luc; Menvielle, Loïck; Bruneau, Julie; Jutras-Aswad, Didier; Bissonnette, Audrey (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2022)
SummaryRestrictions implemented around the world to contain the spread of COVID-19 have had various consequences for workers. Emotional distress, maladaptive behaviours, and issues such as sleep disorders, irritability, and loss of motivation are expected, particularly among employees not used to telework. We wished to find out whether previous telework experience helped workers maintain their quality of life during the lockdown. Data were collected through an anonymous online survey of adult workers ≥ 18 years old in Canada, between May 25, 2020, and June 26, 2020. The survey was completed by 604 teleworkers, 66.8% of whom had not teleworked before the lockdown. The respondents provided self-reported data on sociodemographics, mental health issues, and quality of life. We assessed changes in quality of life by using paired t-tests and linear regression to identify significant determinants. Our analysis shows a decline during the lockdown in all quality of life indicators: stress, irritability, sleep quality, motivation, ability to undertake projects, and surfing the Internet without a specific goal (p < 0.001). The decline was mainly driven not by lack of previous telework experience but rather by a combination of three factors: having young children at home, having a high frequency of telework, and being a man.AbstractCOVID-19 lockdowns have significantly impacted workers over the last year. In particular, telework has significantly changed the way work is done. We wished to find out whether previous telework experience helped workers maintain their quality of life during the lockdowns. By analyzing data collected from Canadian workers in the spring of 2020, we found that quality of life indicators significantly declined during the lockdown, and that previous telework experience did little to protect workers. We conclude that quality of life declined the most among teleworkers who had young children at home during the lockdown and who also had a high frequency of telework. This combination seems to have been more detrimental to men than to women.